ANALISIS PRESEPSI PENGGUNAAN APLIKASI DIGITAL BANKING OLEH MAHASISWA FEBI UNTUK PEMBAYARAN UKT DI UIN GUSDUR - Putri, Fariska Amalia; Syamsuddin (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This research tries to find out how UKT (Single Tuition Fee) payments at UIN Gusdur Pekalongan are perceived by students majoring in Islamic banking FEBI (Faculty of Economics and Islamic Business). Primary data used in this study was collected through interviews with respondents using descriptive qualitative methods. A technical tool called "digital banking" was created to speed up consumer transactions. One of them, driven by the increasing use of the internet in society, is the digitalization of banking in Indonesia.  Then one of the targets is students, who are expected to use and trust the financial system with its innovation in the form of digital banking applications as a transaction instrument used in everyday life, especially in UKT (Single Tuition Fee) payments.